KAJIAN LITERATUR RESISTENSI DALAM PENGAMBILAN KEBIJAKAN PEMBANGUNAN SERTA USULAN STRATEGI DALAM MENGHADAPI RESISTENSI KEBIJAKAN PEMBANGUNAN OLEH PEMERINTAH KABUPATEN INDRAGIRI HILIR - Akbar Alfa , Rezky Kinanda (Badan Perencanaan Pembangunan Daerah Kabupaten Indragiri Hilir Riau, 2019)
The Resistance Movement is a movement that is very typical of the rejection of policies or changes made in an area in which there are humans in it. There are two categories of actors involved in the resistance movement, namely the policy maker and the recipient of the policy. The identity of the perpetrators depends on the case and the location of the case which contains different human characteristics or human communities. The research uses literature review as preparation material for the Government of Indragiri Hilir Regency in dealing with resistance movements. This journal is the result of qualitative research which will explain theoretically the resistance movement. Resistance movement is the movement of a party in making a rejection or resistance to the policy to be made or already made. The results of this study can be used as a discussion of Indragiri Hilir Regency Government in making policies and dealing with resistance movements. This research concludes that poor communication and socialization can spark a desire to resist. The resistance movement becomes stronger when the policy maker is unable or slow in responding to the complaints of the recipient of the policy. Regardless of whether the complaint is wrong or right, rapid response must be done quickly so that there is no misunderstanding that causes greater resistance. The policy makers must identify the causes of resistance because the causes are the basic foundation in developing strategies for handling and resolving conflicts in this resistance movement. So that it can be said that each cause has its own handling strategy.